Hydrothermally deposited Sb2S3 absorber, and a Sb2S3/CdS solar cell with VOC approaching 800 mV - Pokhrel, Dipendra; Mathews, N.R.; Mathew, X.; Rijal, Suman; Karade, Vijay C.; Kummar, Samietha S.; Friedl, Jared; Mariam, Tamanna; Adhikari, Alisha; Song, Zhaoning; Bastola, Ebin; Abasi, Abudulimu; et al. (Solar energy materials and solar cells, 2024)
We report the hydrothermal deposition of Sb2S3 thin film on top of CdS buffer layer, and the fabrication of prototype photovoltaic devices utilizing spiro-OMeTAD as the hole transport layer. The as-deposited films were amorphous, which transformed to polycrystalline after thermal processing. The pristine films were annealed at different temperatures and showed effective recrystallization at 350 °C which resulted in larger grains, intense XRD patterns, and significantly improved device parameters. The obtained VOC of 795 mV is among the highest reported for a Sb2S3 based solar cell. Deep level transient spectroscopy studies detected an electron trap with activation energy 0.61 eV in the pristine annealed absorber, which became deeper (0.66 eV) upon Na incorporation. However, the capture cross-section decreased by an order of magnitude, and the trap density halved. The reduction in the capture cross-section and trap density for the Na-incorporated device coincides with the improved EQE response in the mid- and long-wavelength regions and a 9 % increase in device efficiency. The light intensity dependence of VOC clearly demonstrated that Na incorporation reduced the trap-assisted recombination and facilitated efficient charge transport in the device. •Reporting Sb2S3 based solar cell with VOC close to 800 mV, which is an achievement with respect to the state-of-the-art in this area.•With Na doping, the current collection in the mid- and long-wavelength regions improved, predominantly due to reduction in the capture cross-section and density of a deep trap, leading to 9 % relative increase in device efficiency.